2014
DOI: 10.1177/1357633x14537777
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile phones as a tool for weight loss: a systematic review

Abstract: We conducted a systematic review of the literature on the use of mobile phones for weight loss. A total of 43 studies were identified on obese or overweight adults, aged 18 years or over. After review, ten articles met the inclusion criteria. There were 19-534 participants per study. Participants were from European, Asian and North American regions. The mean body mass index (BMI) of the subjects varied from 22 to 36 kg/m(2). Two studies used text messaging or multimedia messaging. All the other studies used mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 29 publications
2
48
0
5
Order By: Relevance
“…In particular there is limited information regarding the best application characteristics for disadvantaged populations (5). There have been a number of early systematic reviews that examine the efficacy of health application interventions; however, these either focus on weight loss rather than nutrition improvement (10)(11)(12)(13)(14), exclude qualitative and descriptive studies (15,16), and/or include text messaging and Web-based interventions (10,12,13,(16)(17)(18), with none specifically relating to community settings.…”
Section: Introductionmentioning
confidence: 99%
“…In particular there is limited information regarding the best application characteristics for disadvantaged populations (5). There have been a number of early systematic reviews that examine the efficacy of health application interventions; however, these either focus on weight loss rather than nutrition improvement (10)(11)(12)(13)(14), exclude qualitative and descriptive studies (15,16), and/or include text messaging and Web-based interventions (10,12,13,(16)(17)(18), with none specifically relating to community settings.…”
Section: Introductionmentioning
confidence: 99%
“…Flores-Gómez, Bacardí-Gascón, Armendáriz-Anguiano, Pérez-Morales y Jiménez-Cruz (2012), mostraron que la terapia de soporte social puede ser un método eficaz para la pérdida de peso. Aguilar-Martínez et al (2014), mostraron la efectividad del uso de los celulares para la pérdida o el control de peso, dependiendo del uso del software.…”
Section: Introductionunclassified
“…Most of these studies have been of short duration and significantly less than 2 years suggested as necessary to determine effective maintenance of weight loss. 8 We previously examined the quality of 28 popular apps downloaded as part of the top 200 health and fitness apps from the Australian Google Play and iTunes stores. 19 Five factors were evaluated to determine quality, including the credibility of the app developers, the accuracy and coverage of scientific information, the inclusion of technology-enhanced features to support the use of the app (e.g., barcode scanners), usability and their likelihood in changing health behaviors, assessed using Abraham and Michie's Behavior Change Taxonomy.…”
Section: Interventions For Weight Management Using Appsmentioning
confidence: 99%
“…One is the traditional randomized controlled trial, which is generally considered to provide best level of evidence, although a limited number of these have been conducted. 8,10 The commercial app MyFitnessPal ® was used in a randomized controlled trial to test its efficacy when introduced in the primary care setting in the US. After 6 months, there was no significant change in weight in those who received the app and those who did not.…”
Section: Interventions For Weight Management Using Appsmentioning
confidence: 99%